Análisis del uso de las tic´s como herramientas para pontecializar el turismo de la Parroquia La Unión - Rivera Jaramillo, Brigette Lisbeth (2021)
This project is under the topic of analysis of the use of ICTs as tools to enhance tourism in the La Unión parish, today the issues of ICTs are in full swing of use, today the different areas of development are implemented within their activities the use of Tics, Tics are a group or set of tools that allow information processing in an easier and faster way than the traditional way of information processing. In tourism, the use of Tics allows the power to have a powerful tool for tourism promotion and information, today tics within tourism help tourists or people interested in traveling to a tourist to access information on offers and tourist service that promotes different parts of the world regardless of where it is, through tics they can access this information quickly without having to go to a travel agency. La Unión parish has a great tourist potential since it is surrounded by a number of natural resources that can be potentialized as tourist points of the parish but for this it is necessary that tourist promotion strategies are applied within these are the Tics that help the local people and strangers of the parish know the tourist offers that the parish has and offers, and this in turn can increase the economic development of the sector.